2015
DOI: 10.1038/nclimate2728
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of public climate change awareness and risk perception around the world

Abstract: Climate change is a threat to human societies and natural ecosystems, yet public opinion research finds that public awareness and concern vary greatly. Here, using an unprecedented survey of 119 countries, we determine the relative influence of socio-demographic characteristics, geography, perceived well-being, and beliefs on public climate change awareness and risk perceptions at national scales. Worldwide, educational attainment is the single strongest predictor of climate change awareness. Understanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
633
1
43

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 979 publications
(728 citation statements)
references
References 55 publications
(76 reference statements)
51
633
1
43
Order By: Relevance
“…In the case of education, some research has suggested that high level of educational attainment at least in developing countries improves climate awareness (Lee et al 2015). Research in developed countries, however, has pointed out that the more educated individuals are, the more they prefer to rely on their own interpretation and political worldviews rather than established climate science to form their opinion about climate change (Stoknes 2014).…”
Section: Factors Shaping Individual Adaption To Climate Change Adaptamentioning
confidence: 99%
“…In the case of education, some research has suggested that high level of educational attainment at least in developing countries improves climate awareness (Lee et al 2015). Research in developed countries, however, has pointed out that the more educated individuals are, the more they prefer to rely on their own interpretation and political worldviews rather than established climate science to form their opinion about climate change (Stoknes 2014).…”
Section: Factors Shaping Individual Adaption To Climate Change Adaptamentioning
confidence: 99%
“…With respect to adaptation to the changing climate, education is indeed highly relevant since individuals with higher level of education are also more likely to have better awareness of climate risk 84 . Given that climate change is a relatively new form of risk and a rather sophisticated scientific subject, education facilitates the understanding of new ideas and concepts related to climate variability.…”
Section: Education Changes Our Behaviour and Reduces Vulnerabilitymentioning
confidence: 99%
“…But there are also other opinions: according to a Pew study (Stokes et al, 2015), an important amount of people was not really concerned that climate change would hurt them; moreover, Yale University researchers (Lee et al, 2015) recently found that 40% of adults worldwide have never heard of climate change! The Yale study concluded that "educational attainment tends to be the single strongest predictor of public awareness of climate change".…”
Section: Purpose Of the Studymentioning
confidence: 99%